Mine Tailings Perspectives for a Changing World. - Furey, Resa (Society for Mining, Metallurgy & Exploration, Incorporated, 2020)
This book provides summaries of the presentations and discussions at the Mine Tailings: Perspectives for a Changing World symposium, held at the SME 2020 annual conference. It deals with the question of how to best address the risks associated with tailings disposal.
Description based upon print version of record.
Back Cover.
Keywords: Tailings dams.; Dam failures.; elektronické knihy; electronic books